Make your music video and put it online - Safir, Robert (Boston, MA : Course Technology PTR, 2010)
"With the popularity of YouTube, Facebook, Vimeo, MySpaceTV, and other video services, musicians are using the video format more than ever. In fact, making a video and getting it seen is a vitally important part of marketing your music or band. This book will help you learn how to produce a high-quality, high-production value, low-budget music video and let the world know about it through the Internet. First, the book offers suggestions for choosing and recording a song appropriate for video. Then you'll learn the basics of filming the video, post-production editing, music synchronization, and video formats optimized for online video. Finally, you'll learn to upload the video to popular online music and social networking sites and how to drive traffic to your new video masterpiece"--Cover, p. 4.
Creating your music. The process ; Mixing considerations -- Producing your video. Music video cookbook : the ingredients ; Choosing your production methods ; Tools for do-it-yourselfers ; Choosing a video style ; Shooting options ; The video process : pre-production and the shoot ; Post-production -- Posting your masterpiece on the Internet. Making your video Internet-ready ; Evaluating popular online sites ; Working with iTunes videos ; Marketing your music video.
Includes bibliographical references (p. 196-198) and index.
Keywords: Music videos -- Production and direction; Digital video -- Editing -- Data processing; Music videos